2003
DOI: 10.2202/1542-0485.1025
|View full text |Cite
|
Sign up to set email alerts
|

Information Pooling and Collusion: Implications for The Livestock Mandatory Reporting Act

Abstract: This paper develops a conceptual model that analyzes the impact of increasing market transparency under the Livestock Mandatory Reporting Act of 1999 on the incentives for collusion in the U.S. meatpacking industry. More than likely, meatpackers will have asymmetric priors regarding the distribution of livestock prices. Moreover, they lack the incentives to voluntarily reveal their real priors. Thus, the enforcer of the Act faces a problem of asymmetric information regarding the informativeness of publicly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…They concluded prices were twice as volatile under the mandatory system, which was unexpected by the research team. These findings conflict with the expectations by Njoroge (2003) that mandatory price reporting would reduce volatility of slaughter livestock prices. A key to this disparity is 9 Rebuilding requires reducing the number of animals in the meat system to increase the number in the breeding herd.…”
Section: Evaluative Research Since Mandatory Price Reportingcontrasting
confidence: 91%
See 2 more Smart Citations
“…They concluded prices were twice as volatile under the mandatory system, which was unexpected by the research team. These findings conflict with the expectations by Njoroge (2003) that mandatory price reporting would reduce volatility of slaughter livestock prices. A key to this disparity is 9 Rebuilding requires reducing the number of animals in the meat system to increase the number in the breeding herd.…”
Section: Evaluative Research Since Mandatory Price Reportingcontrasting
confidence: 91%
“…Albaek, Møllgaard, and Overgaard (1997) investigated the impact of published firm-specific transactions prices for ready-mixed concrete in three regions of Denmark. Wachenheim and DeVuyst (2001), Azzam (2003), Njoroge (2003), and Njoroge et al (2007) represent similar thinking but without the empirical application. Albaek, Møllgaard, and Overgaard concluded that publication of these prices had the unintended consequences of allowing firms to reduce the intensity of oligopoly price competition, and this led to increased consumer prices for concrete rather than reduced prices as was intended by the regulatory agency.…”
Section: Related Research On Market Impacts From Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…(see, e.g., Albaek et al 1997, Njoroge 2003 3 However, these studies do not explain why firms often oppose mandatory information disclosure. 4 Consequently, when the effect of mandatory information disclosure is insignificant, studies often blame consumers' mistrust, disinterest, or lack of understanding (see, e.g., Hibbard andJewett 1997, Marshall et al 2000).…”
Section: Information Disclosurementioning
confidence: 99%
“…What we learned is that transparency in livestock markets may either promote collusion (Njoroge, 2003), or foster more competitive conduct (Azzam, 2003). 4 As in Jin, firms in the two studies are risk-averse, and accuracy of information lowers risk.…”
Section: Introductionmentioning
confidence: 99%